Pengukuran Kesiapan Industri Minuman Teh Menjangkau Revolusi Industri 4.0 dengan Metode INDI 4.0 - Irna Ekawati; Puji Rahayu (Politeknik ATI Padang, 2021)
Rapid technological developments greatly affect the demand for products and services. So the industry needs to improve to maximize production achievements in order to meet market needs. The development of industry 4.0 provides an opportunity to revitalize the Indonesian manufacturing sector. Moreover, the Ministry of Industry has compiled